The responses of nephrolepis biserrata to copper toxicity - Er, Xin Yi, 1992-, author 609190; Fazilah Abd. Manan, supervisor 294946; Fakulti Biosains dan Kejuruteraan Perubatan 538915 (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2016)
Project Paper (Sarjana Muda Sains (Biologi - Industri)) - Universiti Teknologi Malaysia, 2016